PENGARUH RASIO UTANG TERHADAP EKUITAS DAN PENGEMBALIAN ASET TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prayogi Malikul Akbar; Diajeng Reztrianti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this research is to find out the debt to equity ratio and return on asset simultaneously and partially affects the stock price of food and beverage sub sector companies listed on the Indonesian Stock Exchange This study used the purposive sampling. The results of this study is debt to equity ratio and return on assets simultaneously have a significant effect on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. Meanwhile, partially the debt to equity ratio has a significant negative effect on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange and return on assets has a significant positive effect on stock prices in listed food and beverage sub-sector companies on the Indonesia Stock Exchange.